Household food insecurity after the early monsoon flash flood of 2017 among wetland (Haor) communities of northeastern Bangladesh: A cross-sectional study - Parvez, Mahmood; Islam, Mir Raihanul; Dey, Nepal C. (Wiley, 2022)
The livelihoods of wetland (Haor) communities living in northeastern region of Bangladesh are largely dependent on agriculture. Unseasonably heavy rainfall in Haor basin and upstream Indian catchments triggered a devastating early monsoon flash flood in Haor basin at the beginning of April in 2017, which destroyed the nearly ready-to-harvest annual rice crop and resulted in significant income loss of Haor dwellers. The present study aims at assessing post-flood household food insecurity and the factors associated with it in the aftermath of this flash flood. A cross-sectional study design was adopted, and a survey covering 1845 flood-affected households was conducted to measure the post-flood household food insecurity. A set of questionnaires was adopted from Household Food Insecurity Access Scale (HFIAS) to assess the level of household food insecurity, and a modified poisson regression model was used to identify the risk factors of household food insecurity. A staggering 62% of the surveyed households were found food insecure following the flash flood. Being ultra-poor, loss of livestock in flood, household head's occupation being natural resource-based, and household reliance on market purchase of food were identified as significant risk factors of post-flood household food insecurity. Household being headed by relatively younger, educated people, and household owning agricultural land were found to be protective against post-flood food insecurity. Therefore, post-flood emergency programs, especially the food assistance programs should be designed prioritizing these most food insecure groups instead of considering household poverty as the only selection criteria. As a long-term plan, a multi-sectoral approach focusing on disaster risk reduction by taking into account the risk of disaster-induced food insecurity is essential to reduce the vulnerability of wetland communities.